A K-MEANS ALGORITHM FOR THE IMMIGRATION RESIDENTIAL PERMIT - Assiroj, Priati; Pribadhi, I.A; Rizal S, Mohammad (Jurnal Ilmiah Kajian Keimigrasian, 2023)
Information technology utilization is increasing rapidly and massive, it falls within the realm of Immigration. Information technology has become one of the solutions to improve the performance index of Indonesian Immigration. Its utilization is not only at the immigration border but also at the Immigration Office, for example at the Immigration Office of Kediri. Data mining technology is utilized in finding and making a pattern of permit residence in its jurisdiction. We found the optimal cluster is 3. It is based on the Davies Bouldin index (DBI) that we got 0.184. There is a similarity between Cluster 1 and Cluster 3, but we found that the difference between Cluster 1 and Cluster 3 is in Cluster 1 foreigners stay in Kediri city and Kediri regency, as for Cluster 3 foreigners stay in Jombang regency, Nganjuk, etc.